Metanephric stromal tumor with BRAF V600E mutation in an adult patient: Case report and literature review - Fan, Yuqian; Yu, Jingjing; Zhao, Ming (Frontiers in Oncology, 2022)
Metanephric stromal tumor (MST) is a rare, benign pediatric renal neoplasm of uncertain histogenesis that belongs to the metanephric family of tumors. MST involving adult patients is very uncommon, which could cause significant diagnostic confusions. Recent molecular studies have revealed recurrent BRAF mutations in MST in pediatric patients which may serve as powerful diagnostic tools for distinguishing MST from other renal stromal tumors. We present a BRAF-mutated MST in an adult patient with a brief review of the pertinent literature. To our knowledge, our case represents to date the sixth report of adult MST and the first adult MST proven to harbor BRAF mutation. This is a 41-year-old man who was incidentally identified to have a left renal mass by ultrasonography. He had a 5-year history of hypertension which could be controlled with oral antihypertensive drug. Partial nephrectomy was performed which demonstrated a 2.6-cm, oval, circumscribed mass with a fibrotic and firm texture. Microscopic examination showed a hypocellular, spindle cell neoplasm with entrapped nephrons, within a predominantly fibrous and focally myxoid stroma. Foci of hyalinized stroma surrounding entrapped native renal tubules or blood vessels to form concentric collarettes-like structures, and small-sized arterioles showing angiodysplasia, were observed. Immunostains showed the tumor cells to be diffusely positive for CD34. Fluorescence in-situ hybridization analysis was negative for rearrangements involving both the EWSR1 and FUS loci. Targeted next-generation sequencing disclosed a pathogenic mutation of BRAF exon15: c.1799T>A (p.V600E). The patient’s hypertension normalized without oral antihypertensive drugs 2 months postoperatively and he was in good status 12 months after the surgery. Our case highlights the diagnostic dilemma of MST occurring in adults and points to the usefulness of molecular detection of BRAF mutation for arriving at accurate diagnosis.